Effect of axial sinusoidal size variation on the modal characteristics of an annular optical fiber - Singh V.; Prasad B.; Ojha S.P. (My University, 2025)
This paper considers a new lightguide with a circular annular core cross section varying periodically in size along the propagation axis. We report an analytical study of the modal properties of this structure using the weak guidance approximation and considering rector boundary conditions. The characteristic eigenvalue equation is derived. As expected, the z-component of the propagation vector β is found to depend on the variable z, the axial coordinate. The propagation constant β is computed and plotted against z for some low-order modes (modal index v = 0). These curves show an oscillatory periodic behavior. © 2001 John Wiley & Sons, Inc. Microwave Opt Technol Lett.